Amount of bird suitable areas under climate change is modulated by morphological, ecological and geographical traits - Mota, Flávio Mariano Machado; Heming, Neander Marcel; Morante-Filho, José Carlos; Talora, Daniela Custódio (Frontiers in Ecology and Evolution, 2022)
Biodiversity is already experiencing the effects of climate change through range expansion, retraction, or relocation, potentializing negative effects of other threats. Future projections already indicate richness reduction and composition modifications of bird communities due to global warming, which may disrupt the provision of key ecological services to ecosystem maintenance. Here, we systematically review the effect of morphological, ecological, and geographical traits on the amount of future suitable area for birds worldwide. Specifically, we tested whether body mass, diet, habitat type, movement pattern, range size, and biogeographic realm affect birds’ suitable area. Our search returned 75 studies that modeled the effects of climate change on 1991 bird species. Our analyses included 1661 species belonging to 128 families, representing 83% of the total, for which we were able to acquire all the six traits. The proportion of birds’ suitable area was affected by range size, body mass, habitat type, and biogeographic realm, while diet and movement pattern showed lower relative importance and were not included in our final model. Contrary to expectations, the proportion of birds’ suitable area was negatively related to range size, which may be explained by higher climatic stability predicted in certain areas that harbor species with restricted distribution. In contrast, we observed that birds presenting higher body mass will show an increase of the proportion of suitable area in the future. This is expected due to the high exposure of smaller birds to environmental changes and their difficulty to keep thermoregulation. Our results also indicated a low proportion of suitable area to forest-dependent birds, which is in accordance with their higher vulnerability due to specific requirements for reproduction and feeding. Finally, the proportion of suitable area was low for birds from Oceania, which is expected since the region encompasses small islands isolated from continents, preventing their species from reaching new suitable areas. Our study highlights that different traits should be considered when assessing extinction risk of species based on future projections, helping to improve bird conservation, especially the most vulnerable to climate change.